Psychoanalysis and History in Conversation: A Dialogue with Thomas Kohut. Issue 1 (2nd January 2019) - Frie, Roger; Kohut, Thomas
Abstract : In what ways do the fields of psychoanalysis and history interact and what can they learn from each other? In the attempt to bring psychoanalysis and history into conversation, I enter into dialogue with the German historian and psychoanalyst by training, Thomas Kohut. We discuss the challenges facing psychoanalysis today; Kohut's own history in relation to the evolution of psychoanalysis and the work of his father, Heinz Kohut; and the theme of German history and the Holocaust. We explore ways of overcoming the obstacles for cross-disciplinary dialogue and consider the importance of psychoanalytic understanding and empathy.